2014
DOI: 10.1007/s40798-014-0004-6
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Exercise in Preventing Injury in Adult Male Football: A Systematic Review of Randomised Controlled Trials

Abstract: Background: Injury prevention measures might reduce the impact of injury on footballers and football clubs. Increasing research has evaluated the use of exercise for injury prevention. However, research has focused on adolescent females. No high-quality systematic reviews have evaluated the efficacy of all forms of exercise on preventing injury in adult male football.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…HSIs decrease the individual/collective performance and has a negative financial impact (Hickey, Shield, Williams, & Opar, 2014; Nouni‐Garcia et al, 2019). This has motivated the scientific community to pursue a better understanding of why HSIs occur and how to optimize prevention (Porter & Rushton, 2015). However, to date, only the history of hamstring injury has been consistently identified as a HSI risk factor (de Visser, Reijman, Heijboer, & Bos, 2012; van Beijsterveldt, van de Port, Vereijken, & Backx, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…HSIs decrease the individual/collective performance and has a negative financial impact (Hickey, Shield, Williams, & Opar, 2014; Nouni‐Garcia et al, 2019). This has motivated the scientific community to pursue a better understanding of why HSIs occur and how to optimize prevention (Porter & Rushton, 2015). However, to date, only the history of hamstring injury has been consistently identified as a HSI risk factor (de Visser, Reijman, Heijboer, & Bos, 2012; van Beijsterveldt, van de Port, Vereijken, & Backx, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that this type of program can be effective in reducing injury rates in sports involving both lower- and upper-limbs 9 10 11 . However, recent systematic reviews concluded that there is limited scientific evidence to support exercise-based strategies to prevent injuries in football players 34 35 . In this regard, a recent umbrella review concluded that the effectiveness of injury prevention programs might depend on the included exercises, with some exercises such as plyometric, technique or functional exercises offering almost no evidence to support their effectiveness 10 .…”
Section: Discussionmentioning
confidence: 99%